2015
DOI: 10.1111/cas.12821
|View full text |Cite
|
Sign up to set email alerts
|

Declining trends in prevalence of Helicobacter pylori infection by birth‐year in a Japanese population

Abstract: Gastric cancer incidence and mortality have been decreasing in Japan. These decreases are likely due to a decrease in prevalence of Helicobacter pylori infection. Our aim was to characterize the trends in prevalence of H. pylori infection focused on birth‐year. We carried out a cross‐sectional study that included 4285 subjects who were born from 1926 to 1989. We defined H. pylori infection by the serum H. pylori antibody titer. Individuals having H. pylori infection and those with negative H. pylori antibody t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 29 publications
4
42
1
Order By: Relevance
“…In the present study, the results in HP-negative patients were similar to those in the total patient group, indicating that HP infection is less likely to affect the short-term effect of gastric acid suppressants on dyspeptic symptoms. The frequency of HP-positive patients in the present study was 13 , similar to that previously reported in the Japanese population 31 , so that our ndings may be generalizable to the Japanese population. However, because of the small sample size of the present study, larger studies are needed to con rm our ndings.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the results in HP-negative patients were similar to those in the total patient group, indicating that HP infection is less likely to affect the short-term effect of gastric acid suppressants on dyspeptic symptoms. The frequency of HP-positive patients in the present study was 13 , similar to that previously reported in the Japanese population 31 , so that our ndings may be generalizable to the Japanese population. However, because of the small sample size of the present study, larger studies are needed to con rm our ndings.…”
Section: Discussionsupporting
confidence: 91%
“…Japan has shown a decrease in H. pylori prevalence, similar to Korea. In several birth cohort studies from Japan, Japanese individuals born before 1950 showed a H. pylori prevalence rate of 80%‐90%, but those born during the 1980s showed a H. pylori prevalence of 10%‐20% 14, 15. Recent Japanese studies reported that the H. pylori seropositivity in junior high school students was only 3%‐5% 16, 17.…”
Section: Discussionmentioning
confidence: 99%
“…A cross‐sectional study in Japan including 4285 subjects born between 1926 and 1989 revealed a permanent decline in H. pylori seroprevalence. The authors estimated the birth‐year percent change (BPC) for respective birth cohorts . The highest prevalence was in individuals born between 1927 and 1949 where prevalence was 54.0% and 42.0%, respectively, with a BPC of −1.2%.…”
Section: Prevalence Of H Pylori In the General Populationmentioning
confidence: 99%
“…This was followed by a rapid decline in those born between 1949 (42.0%) and 1961 (24.0%) (BPC −4.5%,), but in further birth cohorts born between 1961 (24.0%) and 1988 (14.0%), the BPC was −2.1%. The decline in prevalence could reflect improvements in social infrastructure and sanitary conditions during childhood, and these included municipal water supply introduction between 1950 and 1970 . In parallel with the decline of H. pylori prevalence, there was also a decline in subjects with high‐risk precancerous lesions (defined by pepsinogen levels and H. pylori prevalence) …”
Section: Prevalence Of H Pylori In the General Populationmentioning
confidence: 99%